Faktor Penentu Setting Fisik Dalam Beraktifitas Di Koridor Jalan Sebagai Ruang Publik (Studi Kasus Kampung Kauman Desa Pakuncen Kabupaten Nganjuk) - Ardiansari, Erisa; Ernawati, Jenny; Nugroho, Agung Murti (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2015)
The development of a village to be reduced along with the erosion of cultural values and traditions of their ancestors. In the allotment of a village for the first time in the spotlight is the hall way, be interesting if the tersebeu corridor there are various activities that becomes the center point of a village or town. This study took a study in the Village Pakuncen Nganjuk. Where in the village there is a road corridor is quite interesting, because there is a historic building that became a benchmark for the appearance of the village. It is necessary for the arrangement of the physical setting of the corridor in order to meet their needs as a public space that can accommodate activities that occur in buildings in the corridor area. The cornerstone of the theory used in this research is the theory of the behavior setting with descriptive qualitative method. With the method centered place and person-centered maps maps can be obtained results form the physical arrangement of the road corridor settings that affect day-to-day activities that occur.Keywords : Road corridors, public spaces, activities and behavior